EXPLORING COVID-19 AND SOCIAL CONFLICT IN AFRICA: NIGERIA AS A CASE STUDY (Glocalism: Journal of Culture, Politics and Innovation, 2024)
There are many dimensions to conflict in Africa. It depends on the nature of the underlying demography, heterogeneity, and historical context of the state’s social and political problems. The impact of the coronavirus has greatly affected the socioeconomic structure and governance system in Africa, leading to social conflicts. Moreover, the social conflict led to deaths, job losses, and human capital reductions, resulting in economic catastrophes in South Africa, Egypt, and Ethiopia, among others. In Nigeria, the government was unable to cushion the impact of Covid-19, frustrated by the issues of poverty and inequality, wherein the masses were pounded with hunger and insecurity; a corrupt policing system precipitated the social unrest in 2020. Nigeria’s social issues, coupled with the shock of Covid-19, cumulated into protest actions, looting, and police brutality. The government’s inadequate response to the political crisis and state of unrest greatly influenced the public’s belief and outlook on social concerns. The research postulates the following question: how did the social conflict in Africa and Nigeria become overheated during Covid-19? The paper adopts a qualitative method that explores existing literature and media sources on social conflicts and Covid-19 in Africa and Nigeria. The study anchors its theoretical framework on the fragile state theory. The paper concludes that Nigeria’s weakened socioeconomic structure met with the shock of the horror of Covid-19, which sparked social conflict in the country.
Keywords: Africa; Covid-19; governance; social conflict; sustainable development